Evaluating the Prevalence of Type 2 Diabetes, Impaired Fasting Glucose, and Impaired Glucose Tolerance in the First-degree Family Members of the Diabetic Patients - Najafipour, Dr. Farzad (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Type 2 diabetes is a genetic disorder, but the gene or genes involved in the development of this diabetes have not been well identified so far. In most studies, diabetes has been reported as one of the most common causes of mortality and disability in communities. The probability of diabetes in the first-degree family members of the diabetic person is 30%, which many of them are asymptomatic and unaware of their diabetes. Methodology: In this research, the first-degree family members of type 2 diabetic people were examined, and screening was performed to find impaired glucose tolerance (IGT) and impaired fasting glucose (IFG) diabetes. In this research, 174 families (1556 people aged over 30 years) were examined, which 1232 of them were alive. Fasting blood sugar (FBS) test and oral glucose tolerance test (OGTT) were also used in this regard. Results: The results of this research revealed that 1232 people were alive and 324 died, which 343 (27.9%) of the alive people and 82 of dead people (25.3%) were diabetic. Moreover, 179 (14.5%) had IFG and 89 (7.2%) had IGT. The percentage of offspring and sibling involvement in this sample was 32.9% and 22.1%, respectively. The highest number of diabetic people was seen in the age group of 41–49 years. In this research, it was revealed that the risk of diabetes would be higher in children, if both parents are involved. The percentage of diabetes was higher in females than that in males (32.4% vs. 22.2%). Investigating the diabetes involvement among the first-degree family members also indicated that the highest percentage of diabetes belonged to sisters-brothers (siblings) (41.95%) and the lowest percentage belonged to father-son (10.9%). Conclusion: The incidence of diabetes in most communities is 8–10%. In the case of the development of type 2 diabetes in one of the family members, the incidence of diabetes in other family members increases by 30%. Thus, screening should be performed in all family members of type 2 diabetic person continuously so that the disease to be immediately diagnosed and treated to prevent major complications of diabetes.